Structure-phase status of the high-entropy AlNiNbTiCo alloy; Russian Physics Journal; Vol. 67, No. 2 - Abzaev Yu. A. Yury Afanasjevich; Medich Zh. Zharko; Koptsev M. Maksim; Laptev R. S. Roman Sergeevich; Lider A. M. Andrey Markovich; Lomygin A. D. Anton Dmitrievich; Klopotov A. A. Anatoly Anatoljevich (2024, 2024)
Title screen